Specific and Aspecific Molecular Checkpoints as Potential Targets for Dismantling Tumor Hierarchy and Preventing Relapse and Metastasis Through Shielded Cytolytic Treatments - Manzo, Giovanni (Frontiers in Cell and Developmental Biology, 2021)
I have recently theorized that several similarities exist between tumor process and embryo development. Starting from an initial cancer stem cell (CSC0), similar to an embryonic stem cell (ESC), after implantation in a niche, primary self-renewing CSCs (CSC1s) would arise, which then generate secondary proliferating CSCs (CSC2s). From these epithelial CSCs, tertiary mesenchymal CSCs (CSC3) would arise, which, under favorable stereo-trophic conditions, by asymmetric proliferation, would generate cancer progenitor cells (CPCs) and, then, cancer differentiated cells (CDCs), thus giving defined cell heterogeneity and hierarchy. CSC1s-CSC2s-CSC3s-CPCs-CDCs would constitute a defined ‘tumor growth module’, able to generate news tumor modules, forming a spherical a-vascular mass, similar to a tumor-sphere. Further growth in situ of this initial tumor would require implantation in the host and vascularization, through over-expression of some a-specific checkpoint molecules, such as CD44, ID, LIF, HSP70, HLA-G. To expand and spread in the host tissues, such a vascularized tumor would then carry on a real growth strategy, based on other specific checkpoint factors, such as those contained in the extracellular vesicles (EVs), namely miRNAs, mRNAs, lncRNAs, integrins. These EV components would be crucial in tumor progression, because they can mediate intercellular communications in the surrounding micro-environment and systemically, dictating to recipient cells a new tumor-enslaved phenotype, thus determining pre-metastatic conditions. Moreover, by their induction properties, EV contents could also frustrate in time the effects of cytolytic tumor therapies, where EVs released by killed CSCs might enter other cancer and non-cancer cells, thus giving chemo-resistance, non-CSC/CSC transition (recurrence) and metastasis. Thus, anti-tumor cytotoxic treatments, ‘shielded’ from the EV specific checkpoints by suitable adjuvant agents, simultaneously targeting the aforesaid a-specific checkpoints, should be necessary for dismantling the hierarchic tumor structure avoiding recurrence and preventing metastasis.